Is seborrhoeic dermatitis associated with a diffuse, low‐grade folliculitis and progressive cicatricial alopecia?. (5th March 2015) - Pitney, Lucy; Weedon, David; Pitney, Michael
Abstract: An association between adult scalp seborrhoeic dermatitis and cicatricial hair loss has not previously been convincingly established. This study seeks to demonstrate a unique relationship between a clinically identifiable chronic scalp dermatitis‐folliculitis with the characteristic histological features of low‐grade inflammatory fibrosing alopecia, resulting in a distinctive progressive cicatricial alopecia which we believe is prevalent and hitherto unrecognised, and befits the description of seborrhoeic folliculitis. The clinical, epidemiological and histopathological features of seborrhoeic folliculitis are demonstrated to establish its unique status among the disorders of adult diffuse cicatricial alopecia.